2019
DOI: 10.1002/hep.30242
|View full text |Cite
|
Sign up to set email alerts
|

MERIT: Systematic Analysis and Characterization of Mutational Effect on RNA Interactome Topology

Abstract: Our results provide a valuable resource for characterizing somatic mutation-perturbed protein-RNA regulatory networks in HCC, yielding valuable insights into the genotype-phenotype relationships underlying human cancer, and potential biomarkers for precision medicine. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Recent studies have suggested that dysregulation of multiple RNAs is involved in the development and progression of HCC and could act as a risk predictor of HCC patient survival . This indicates the possible importance of RNA‐binding proteins (RBP), key posttranscriptional regulators that control the fate of nearly every RNA transcript in a cell, in HCC ; indeed, aberrant expression of RBP is observed in human cancers, including HCC, and plays a prominent role in the development and progression of HCC by inducing dysregulation of the HCC transcriptome . Therefore, in‐depth research on the dysregulation of the multiple RNAs mediated by RBP will aid in better understanding RBP‐RNA interaction networks in HCC, which is anticipated to provide valuable insights into early diagnostic biomarkers and reliable therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that dysregulation of multiple RNAs is involved in the development and progression of HCC and could act as a risk predictor of HCC patient survival . This indicates the possible importance of RNA‐binding proteins (RBP), key posttranscriptional regulators that control the fate of nearly every RNA transcript in a cell, in HCC ; indeed, aberrant expression of RBP is observed in human cancers, including HCC, and plays a prominent role in the development and progression of HCC by inducing dysregulation of the HCC transcriptome . Therefore, in‐depth research on the dysregulation of the multiple RNAs mediated by RBP will aid in better understanding RBP‐RNA interaction networks in HCC, which is anticipated to provide valuable insights into early diagnostic biomarkers and reliable therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that dysregulation of multiple RNAs is involved in the development and progression of HCC and could act as a risk predictor of HCC patient survival [7,8]. This indicates the possible importance of RNA-binding proteins (RBP), key posttranscriptional regulators that control the fate of nearly every RNA transcript in a cell, in HCC [7][8][9][10]; indeed, aberrant expression of RBP is observed in human cancers, including HCC, and plays a prominent role in the development and progression of HCC by inducing dysregulation of the HCC transcriptome [7][8][9][10]. Therefore, in-depth research on the dysregulation of the multiple 396 H Kang, S Heo et al Polypyrimidine tract-binding protein 1 (PTBP1), also known as heterogeneous nuclear ribonucleoprotein (hnRNP) I, is one of the most investigated multifunctional RBP, regulating several biological processes including cell structure and motility, protein metabolism and modification, immunity, and the cell cycle [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The mutational spectrum of RBPs had been analyzed and identified a number of RBPs exhibited significantly mutation in cancer (Neelamraju et al, 2018). Li et al, have also decoded the genome-wide RBP mutational and transcriptomic landscape and yielded valuable insights into the function of RBPs (Li et al, 2019a). All these results suggest that there are prevalent alterations of RBPs in cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unobtrusive nature of the symptoms, nearly 75% of patients present at an advanced stage, leading to a 5-year-survival rate of only 29% in the advanced stage. The rst-line therapy is tumor-debulking surgery followed by platinum-based chemotherapy; however, recurrence occurs in nearly 75% of patients 2 . Moreover, there is no con rmed effective drug for patients following platinum-resistant recurrence.…”
Section: Introductionmentioning
confidence: 99%